Pengaruh Phubbing dan Digital Parenting Terhadap Kecemasan Sosial Siswa Sekolah Menengah Pertama ( SMP) - Aisyah Shabrina Pratomo; Meriam Esterina; Budi Setiawan (Psychopolytan : Jurnal Psikologi, 2025)
This study identifies the relationship between phubbing behavior and digital parenting styles on social anxiety among junior high school students in Purworejo Regency. A quantitative survey method was employed with a sample of 395 students aged 13–15 years (201 males and 194 females) selected through random sampling. Data were collected using validated questionnaires and analyzed using multiple linear regression. The results revealed that phubbing had a significant positive effect on social anxiety (β = 0.617; p < 0.05), while digital parenting had a significant negative effect on social anxiety (β = -0.414; p < 0.05). Simultaneously, both variables exerted a significant influence (F = 7.950; p < 0.05) and were able to explain 57% of the variance in students’ social anxiety (R² = 0.570). These findings highlight that effective digital parenting can mitigate the negative impact of phubbing behavior and contribute to strengthening adolescents’ socio-emotional resilience in the digital era.